Konstruksi dan Identifikasi Properti Psikometris Instrumen Pengukuran Kebahagiaan Berbasis Pendekatan Indigenous Psychology: Studi Multitraitâ€Multimethod - Anggoro, Wahyu Jati; Widhiarso, Wahyu (Faculty of Psychology, Universitas Gadjah Mada, 2010)
The aim of this study was to develop a scale of happiness based on indigenous psychology approach and identify itâ€™s psychometric properties. The research was divided into three step of scenario: 1. happiness construct exploration based on indigenous psychology approach; 2. Develop the construct into a scale of happiness (Likert model); and 3. Identify itâ€™s psychometric properties (reliability and validity). The psychometric properties analyses consist of internal consistency reliability (alphaâ€Cronbach) and construct validity (convergentâ€discriminant). Multitraitâ€multimethod matrix was used on the analysis in order to identify the convergentâ€discriminant validity (including three comparative scales: Selfâ€Esteem Scale Rosenberg, Selfâ€Esteem Inventory Coopersmith, and PGC Morale Scale). The exploration result shows a unique indicators of happiness in the East native culture (N=604). The psychometric properties analysis show the alpha reliability Î±=0.895 and the validity was psychometrically accepted (N=111). The conclusion of this study: happiness is a unique construct that consist of strong contextual aspects and the measurement of a native happiness should used a scale of happiness that based on indigenous psychology approach. Further result will be discussed.